Glass Fiber Plant Design - Mejia, Jose L. (College of Engineering, 1968)
Capacity: 9140 lbs/day -- Total fixed capital investment: P2,271,424 -- Operating cost at maximum production: P 1,686,919 -- Annual sales at maximum production: 3,220,000 -- Pay-out time: 2.2 years -- Maximum annual rate of production: 2,410,000 lbs. -- Break-even point: 34% -- Percent return on investment before taxes: 36.5%